V.1 - Ray,B.N (New Delhi, 2009)
Foundations of Western Political Thought is an energetic, engaged and lucid account of the most important political and social thinkers and the enduring themes of the last two and a half millennia. Written for the undergraduate and graduate students of political science, the book traces the development of political thought from Socrates to Marx. It focuses on individual thinkers and texts and offers original views of theorists and by highlighting those which may have been unjustly neglected. It develops the wider themes of political thought and relations between thinkers over time. Each chapter is intended to present a coherent political theory derived from the works of a classical political thinker.
Keywords: Political thought-Western